Electrospun Ag-decorated reduced GO-graft-chitosan composite nanofibers with visible light photocatalytic activity for antibacterial performance. (July 2022) - Asgari, Shadi; Mohammadi Ziarani, Ghodsi; Badiei, Alireza; Setayeshmehr, Mohsen; Kiani, Mahsa; Pourjavadi, Ali
Abstract: The treatment of water contaminated by bacteria is becoming a necessity. The nanomaterials possessing both intrinsic antibacterial properties and photocatalytic activity are excellent candidates for water disinfection. The powdered form of nanomaterials can be aggregated while embedding the nanomaterials into the NFs can overcome the limitation and enhance the photocatalytic activity and transition from UV-light to visiblelight. Here, graphene oxide (GO) was synthesized, grafted to chitosan, and decorated with silver nanoparticles (Ag NPs) to produce Ag-decorated reduced GO-graft-Chitosan (AGC) NPs. The blends of polyacrylonitrile (PAN) and AGC NPs were prepared in various concentrations of 0.5 wt%, 1.0 wt%, 5.0 wt%, and 10.0 wt% and used to fabricate the electrospun composite NFs. FTIR/ATR, UV–Vis, Raman, XRD, and SEM/EDAX analyses confirmed the successful preparation of the NPs and NFs. The cytotoxicity and antibacterial activity of the composite NFs were received in the order of composite NFs 10.0 wt%˃ 5.0 wt%˃ 1.0 wt%˃ 0.5 wt% in both conditions with/without light irradiation. Their cytotoxicity and antibacterial activity were more under light irradiation compared to the dark. The composite NFs (5.0 wt%) were distinguished as the optimum NFs with cell viability of 80% within 24 h and 60% within 48 h on L929 cells and inhibition zone diameter (IZD) of 12 mm for E. coli and 13 mm for S. aureus after 24 h under the light irradiation. The optimum composite NFs showed thermal stability up to 180 °C and tensile strength of 1.11 MPa with 21.71% elongation at break. Graphical abstract: Image 1 Highlights: Fabrication of electrospun composite NFs through electrospinning of AGC-loaded PAN solutions. The use of composite NFs for water disinfection owing to their antibacterial performance and photocatalytic activity. The achievement of cytotoxicity and antibacterial activity of NFs in the order of 10.0 wt%˃ 5.0 wt%˃ 1.0 wt%˃ 0.5 wt%. Selection of the composite NFs (5.0 wt%) as the optimum NFs due to both good antibacterial activity and low cytotoxicity